Hyperarousal symptoms and decreased right hemispheric frontolimbic white matter integrity predict poorer sleep quality in combat-exposed veterans. (3rd July 2021) - Bottari, Sarah A.; Lamb, Damon G.; Murphy, Aidan J.; Porges, Eric C.; Rieke, Jake D.; Harciarek, Michał; Datta, Somnath; Williamson, John B.
ABSTRACT: Objective: Disrupted sleep is common following combat deployment. Contributors to risk include posttraumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI); however, the mechanisms linking PTSD, mTBI, and sleep are unclear. Both PTSD and mTBI affect frontolimbic white matter tracts, such as the uncinate fasciculus. The current study examined the relationship between PTSD symptom presentation, lateralized uncinate fasciculus integrity, and sleep quality. Method: Participants include 42 combat veterans with and without PTSD and mTBI. Freesurfer and Tracula were used to establish specific white matter ROI integrity via 3-T MRI. The Pittsburgh Sleep Quality Index and PTSD Checklist were used to assess sleep quality and PTSD symptoms. Results: Decreased fractional anisotropy in the right uncinate fasciculus (β = −1.11, SE = 0.47, p < .05) and increased hyperarousal symptom severity (β = 3.50, SE = 0.86, p < .001) were associated with poorer sleep quality. Conclusion: Both right uncinate integrity and hyperarousal symptom severity are associated withsleep quality in combat veterans. The right uncinate is a key regulator of limbic behavior and sympathetic nervous system reactivity, a core component of hyperarousal. Damage to this pathway may be one mechanism by which mTBI and/or PTSD could create vulnerability for sleep problems following combat deployment.